A specific role for phosphoinositide 3-kinase and AKT in osteoblasts? - McGonnell, Imelda M.; Grigoriadis, Agamemnon E.; Lam, Eric W.; Price, Joanne S.; Sunters, Andrew (Frontiers in Endocrinology, 2012)
The phosphoinositide 3-kinase and AKT (Protein Kinase B, PKB) signalling pathway (PI3K/AKT) plays a central role in the control of cell survival, growth and proliferation throughout the body. With regard to bone, and in particularly in osteoblasts, there is an increasing amount of evidence that the many signalling molecules exert some of their bone specific effects in part via selectively activating some of the generic effects of the PI3K/AKT pathway in osteoblasts. There is further data demonstrating that PI3K/AKT has the capacity to specifically cross-talk with other signalling pathways and transcriptional networks controlling bone cells' development in order to fine-tune the osteoblast phenotype. There is also evidence perturbations in the PI3K/AKT pathway may well be responsible for certain bone pathologies. In this review we discuss some of these findings and suggest that the PI3K/AKT pathway is a central nexus in the extensive network of extracellular signalling pathways that control the osteoblast.